Mehr Ungleichheit durch kleinere Haushalte? Der~Zusammenhang zwischen Veränderungen der~Haushaltsstruktur und der~Einkommensverteilung in~Deutschland - Andreas Peichl; Nico Pestel; Hilmar Schneider (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– Income inequality in Germany has been increasing continuously during the past 20 years. In general, this is understood as an increase in inequality of wages due to changes in bargaining power of employees. However, the role of changing household structure is widely neglected. Societal trends like a decline in birth rate and an increase in the risk of divorce affect per capita incomes, which has repercussions for the income distribution even if wages remain constant. The aim of this paper is to quantify the proportion of changing household structures in the increase in inequality. We find that the rise in inequality was indeed more due to demographic trends rather than changes in wages. Moreover, a large part of this increase is compensated by the welfare state.
Keywords: D31; D63; I30; J11; 330; private Haushalte; Familienstruktur - Auswirkungen; Einkommensverteilung - Entwicklung; soziale Ungleichheit; Familiengröße; sozialer Wandel; demografischer Wandel; Haushaltseinkommen; Geburtenrückgang; Kinderzahl; Einkommenseffekte; Familieneinkommen